2022
DOI: 10.20517/jtgg.2021.61
|View full text |Cite
|
Sign up to set email alerts
|

The DNA damage response - from cell biology to human disease

Abstract: Maintenance of DNA integrity is crucial for faithful transmission of the genetic code from generation to generation. Our genetic code is constantly under attack from both endogenous and exogenous sources of DNA damage. To ensure genome stability, cells have developed elegant DNA damage repair mechanisms. Defects in DNA damage repair have been linked to several human diseases including promoting oncogenesis, heritable neurodegenerative and neuromuscular diseases caused by unstable DNA repeats, neuropathies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…Living organisms are continually exposed to sources of DNA damage, both endogenous and exogenous, which can significantly impact health and contribute to various diseases [59]. Studies consistently show that patients with mamary cancer exhibit notably higher levels of initial endogenous DNA damage compared to healthy individuals [59,60,61]. In response to these genetic challenges, cells have evolved complex mechanisms to safeguard genome stability, including base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), homologous recombination (HR), and nonhomologous end-joining (NHEJ) [62,63].…”
Section: Resultsmentioning
confidence: 99%
“…Living organisms are continually exposed to sources of DNA damage, both endogenous and exogenous, which can significantly impact health and contribute to various diseases [59]. Studies consistently show that patients with mamary cancer exhibit notably higher levels of initial endogenous DNA damage compared to healthy individuals [59,60,61]. In response to these genetic challenges, cells have evolved complex mechanisms to safeguard genome stability, including base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), homologous recombination (HR), and nonhomologous end-joining (NHEJ) [62,63].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, intrinsic apoptosis pathway is triggered by DNA and oxidative damage, which are linked with disruption of the mitochondrial membrane potential (MMP), increase of cytochrome c (Cyt c) release, and apoptosis induction ( McDonald et al., 2022 ). Precisely, from the comparison between rhein and Cassia angustifolia , several proteins involved in DNA damage repair were uniquely identified in rhein-treated samples, suggesting a potential genotoxic chemical exposure ( Lam, 2022 ). These are the following:…”
Section: Resultsmentioning
confidence: 99%
“…It is now commonly accepted that when the magnitude of DNA lesions overwhelms the skin's DNA repair capacity, an un-repaired or un-removed mutant may have an opportunity to eventually develop into a skin cancer [21][22][23]. Interestingly, strong sunlight can produce up to 100,000 DNA lesions per skin cell per hour [24][25][26]. It was suggested that the SS, caused by strong sunlight primarily attributed to UVB rays, can overwhelm a skin cell's DNA repair capacity and can potentially trigger the development of skin cancer [10].…”
Section: Ss Overwhelms the Dna Repair Mechanismsmentioning
confidence: 99%